Pengaruh Kualitas Pelayanan Dan Ketepatan Waktu Pengiriman Terhadap Kepuasan Pelanggan Pengguna Jasa JNE Maumere - Theresia Febronia Mbupu; Yoseph D. P. Rangga; Magdalena Silawati Samosir (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This study aimed to (1) understand the overview of service quality and delivery timeliness concerning customer satisfaction; (2) analyze the influence of service quality and delivery timeliness on customer satisfaction, both partially and simultaneously. The population of this study consisted of 667 customers using JNE Maumere services. Using the Slovin formula, the sample size was determined to be 87 respondets. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, specifically multiple linear regression. Hypothesis testing was conducted using the F- test and t-test. Descriptive analysis results indicated that the service quality variable was categorized as very good, the delivery timeliness variable as good, and the customer satisfaction variable as good. The t-test results showed that, partially, the service quality variable had a positive and significant effect on customer satisfaction. In contrast, the delivery timeliness variable had a positive but not significant impact on customer satisfaction. The F-test results demonstrated that the service quality and delivery timeliness variables significantly influenced customer satisfaction. Determination analysis showed that service qulity and delivery timeliness accounted for 92.3% of the variation in customer satisfaction among JNE Maumere service users.